Grazoprevir plus elbasvir in treatment-naive and treatment-experienced patients with hepatitis C virus genotype 1 infection and stage 4–5 chronic kidney disease (the C-SURFER study): a combination phase 3 study. Issue 10003 (17th October 2015) - Roth, David; Nelson, David R; Bruchfeld, Annette; Liapakis, AnnMarie; Silva, Marcelo; Monsour, Howard; Martin, Paul; Pol, Stanislas; Londoño, Maria-Carlota; Hassanein, Tarek; Zamor, Philippe J; Zuckerman, Eli; et al.
Summary: Background: Chronic hepatitis C virus (HCV) infection in patients with stage 4–5 chronic kidney disease increases the risk of death and renal graft failure, yet patients with hepatitis C and chronic kidney disease have few treatment options. This study assesses an all-oral, ribavirin-free regimen in patients with HCV genotype 1 infection and stage 4–5 chronic kidney disease. Methods: In this phase 3 randomised study of safety and observational study of efficacy, patients with HCV genotype 1 infection and chronic kidney disease (stage 4–5 with or without haemodialysis dependence) were randomly assigned to receive grazoprevir (100 mg, NS3/4A protease inhibitor) and elbasvir (50 mg, NS5A inhibitor; immediate treatment group) or placebo (deferred treatment group) once daily for 12 weeks. Randomisation was done centrally with an interactive voice response system. An additional cohort of patients who were not randomised received the same regimen open-label and underwent intensive pharmacokinetic sampling. The primary efficacy outcome was a non-randomised comparison of sustained virological response at 12 weeks (SVR12) after the end of therapy for the combined immediate treatment group and the pharmacokinetic population with a historical control. The primary safety outcome was a randomised comparison between the immediate treatment group and the deferred treatment group. After 4 weeks of follow-up (study week 16), unmasking occurred and patients in the deferred treatment group received grazoprevir and elbasvir. The primary efficacy hypothesis was tested at a two-sided significance level (type I error) of 0·05 using an exact test for a binomial proportion. Safety event rates were compared between immediate treatment and deferred treatment groups using the stratified Miettinen and Nurminen method with baseline dialysis status as the strata. The study is registered atClinicalTrials.gov, numberNCT02092350 . Findings: 224 patients were randomly assigned to the immediate treatment group with grazoprevir and elbasvir (n=111) or the deferred treatment group (n=113), and 11 were assigned to the intensive pharmacokinetic population. Overall, 179 (76%) were haemodialysis-dependent, 122 (52%) had HCV genotype 1a infection, 189 (80%) were HCV treatment-naive, 14 (6%) were cirrhotic, and 108 (46%) were African American. Of the 122 patients receiving grazoprevir and elbasvir, six were excluded from the primary efficacy analysis for non-virological reasons (death, lost-to-follow-up [n=2], non-compliance, patient withdrawal, and withdrawal by physician for violent behaviour). No patients in the combined immediate treatment group and intensive pharmacokinetic population and five (4%) in the deferred treatment group discontinued because of an adverse event. Most common adverse events were headache, nausea, and fatigue, occurring at similar frequencies in patients receiving active and placebo drugs. SVR12 in the combined immediate treatment group and intensive pharmacokinetic population was 99% (95% CI 95·3–100·0; 115/116), with one relapse 12 weeks after end of treatment when compared with a historical control of 45%, based on meta-analyses of interferon-based regimens used in clinical trials of patients infected with HCV who are on haemodialysis. Interpretation: Once-daily grazoprevir and elbasvir for 12 weeks had a low rate of adverse events and was effective in patients infected with HCV genotype 1 and stage 4–5 chronic kidney disease. Funding: Merck Sharp & Dohme Corp.